2006
DOI: 10.1515/revneuro.2006.17.1-2.163
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the Roles of NMDA Receptor and Hippocampus in Rats' Spatial Learning: The Effects of Environmental Familiarity and Task Familiarity

Abstract: In this study, we compared the effects of MK-801 and hippocampal lesions on re-training of Morris water maze place task in familiar and novel environments in rats. In Experiment 1, rats were pre-trained with the place task. After acquiring the task, rats were re-trained with the same task in a familiar environment following MK-801 injection, and were then trained with the same task in a novel environment following MK-801 injection. In the familiar environment, MK-801 had no effect, but in the novel environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Spatial pretraining did not ameliorate the AP5-induced acquisition deficits in a novel spatial task in a novel environment. The present results were consistent with our earlier studies (Uekita & Okaichi, 2005; Uekita, Okaichi, & Okaichi, 2006), demonstrating that hippocampal NMDA receptors are required for the formation of spatial representation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Spatial pretraining did not ameliorate the AP5-induced acquisition deficits in a novel spatial task in a novel environment. The present results were consistent with our earlier studies (Uekita & Okaichi, 2005; Uekita, Okaichi, & Okaichi, 2006), demonstrating that hippocampal NMDA receptors are required for the formation of spatial representation.…”
Section: Discussionsupporting
confidence: 94%
“…Concerning the methods of NMDA blockade, in our earlier studies we injected MK-801 intraperitoneally (Uekita & Okaichi, 2002, 2005; Uekita et al, 2006). Therefore, we could not confirm if the impairment in spatial tasks was a result of the blockade of the hippocampal NMDA receptor, since systemically injected MK-801 blocks the NMDA receptors as well as those in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains uncertain what exactly newly generated neurons contribute to hippocampus‐dependent learning, this finding suggests that the learning produced by the Morris water task training under reduced‐cue hidden platform conditions may be inhibitory to adult neurogenesis. Glutamatergic signaling via NMDA receptors plays a role in spatial learning (Uekita et al, 2006) and has a complex regulatory role in adult neurogenesis (Nacher and McEwen, 2006). Both increases (Joo et al, 2007) and decreases (Cameron et al, 1995) in adult neurogenesis have been reported following modulation of NMDA receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…A study looking at memory dysfunction found that GF mice, on exposure to Novel Object Recognition and T-maze exploration tests, lacked non-spatial and working memory [145] which are believed to involve NMDARs in the hippocampus [146][147][148][149]. In addition, the animals exhibited a decrease in hippocampal BDNF expression compared to colonised controls consistent with evidence that the microbiota can modulate cerebral neurotrophins [81].…”
Section: Microbial Regulation Of Bdnf and Nmdarsmentioning
confidence: 72%